Shinto : the way home - Kasulis, Thomas P., 1948- (Dimensions of Asian spirituality., 2004)
Scholarly studies on Shinto usually focus only on one of its dimensions: Shinto as a 'nature religion', an 'imperial state religion', a 'primal religion', or a 'folk amalgam of practices and beliefs'. Thomas Kasulis explains how these different aspects interrelate.